El cuerpo contra la pared : representaciones del cuerpo en la imagen grafiti - Vargas Rodríguez, Alberto (Editorial UTADEO, 2017)
The body against the wall is a reading of the representations of the human body in the graffiti image with the lenses of the history of art, aesthetics, sociology and literature; Explored with the purpose of trying to understand something of the contemporary social and cultural universe. Within the wide spectrum of the graffiti image stands a prolific slope in which the motive of primordial representation is the human body. Painted, stenciled, adhered on the walls, these images are ephemeral tattoos in urban skin; In them the body becomes a form of language through which they range from advertising messages to diatribes on the status quo, and from individual opinions and desires to collective imaginaries.